Classification of Malaysian Architecture Revisited - Julaihi Wahid; Azli Bin Abdullah; Basseem Salleh; Mohd Arar (RUAS, 2021)
This paper attempts to portray the classification of Malaysian architecture according to the trends and changes along with the advancement of the economy, technology and growth of architecture schools in Malaysia. The faces of Malaysian architecture are very much influenced by graduates in architecture returning from overseas and the establishment of the Malaysian Institute of Architects. Malaysia is blessed with natural beauty and resources that enable it to be independent. The hot-wet equatorial climate of Malaysia and its high humidity together with the abundance of timber and other cheap building materials enable builders and architects alike to experiment with the built forms. The traditional and vernacular architecture that has been crystallized in the colonial style by the pioneer British architects who designed the government quarters and other government buildings in Malaysia revealed the attention towards the climatic factors and the style that later developed into modern and post-modern style that appear in the residential design of the Malaysian landscape today. This paper employs an exploratory technique from earlier writings and longitudinal historical evidences of Malaysian architecture, visual surveys from the digital media and verbal comments from the practising Architects interviewed. The finding shows that the Malaysian Architecture can be classified according to era, style and contemporary trends influenced by the changes in the world.